2022
DOI: 10.1111/mec.16635
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering Eurasian otter (Lutra lutra L.) and seal (Phoca vitulina L.; Halichoerus grypus F.) diet: Metabarcoding tailored for fresh and saltwater fish species

Abstract: Long‐lived top predators shape biodiversity structure in their ecosystems and predator–prey interactions are critical in decoding how communities function. Studies on the foraging ecology of seals and Eurasian otters in Western Europe are outdated and most studies solely performed traditional hard part analysis. Molecular metabarcoding can be used as an innovative noninvasive diet analysis tool, which has proven efficient and complementary to hard part analysis, however, lacking application in the wider North … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 136 publications
0
5
0
Order By: Relevance
“…Heartworms are common in harbour seals and frequently infect individuals found stranded along the German North-and Baltic Sea coasts (Claussen et al, 1991;Lehnert et al, 2007Lehnert et al, , 2015 and adjacent waters (Lunneryd, 1992). However, they were so far not reported from grey seals which share their habitat, diet preferences and haul-outs with harbour seals (Brasseur, 2017;Damseaux et al, 2021;Boyi et al, 2022). The insect seal louse Echinophthirius (E.) horridus infects both harbour and grey seals and occur regularly on both species throughout the study area (Zimmermann and Nebel, 1975;Lehnert et al, 2015) and in adjacent waters (Thompson et al, 1998;Morick et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Heartworms are common in harbour seals and frequently infect individuals found stranded along the German North-and Baltic Sea coasts (Claussen et al, 1991;Lehnert et al, 2007Lehnert et al, , 2015 and adjacent waters (Lunneryd, 1992). However, they were so far not reported from grey seals which share their habitat, diet preferences and haul-outs with harbour seals (Brasseur, 2017;Damseaux et al, 2021;Boyi et al, 2022). The insect seal louse Echinophthirius (E.) horridus infects both harbour and grey seals and occur regularly on both species throughout the study area (Zimmermann and Nebel, 1975;Lehnert et al, 2015) and in adjacent waters (Thompson et al, 1998;Morick et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Heartworms are common in harbour seals and frequently infect individuals found stranded along the German North- and Baltic Sea coasts (Claussen et al ., 1991 ; Lehnert et al ., 2007 , 2015 ) and adjacent waters (Lunneryd, 1992 ). However, they were so far not reported from grey seals which share their habitat, diet preferences and haul-outs with harbour seals (Brasseur, 2017 ; Damseaux et al ., 2021 ; Boyi et al ., 2022 ). The insect seal louse Echinophthirius ( E .)…”
Section: Discussionmentioning
confidence: 99%
“…Ando et al (2022) used fecal DNA metabarcoding from 7 species of ducks (329 samples) to show strong niche partitioning of plant diet across species but opportunistic foraging when invertebrates were the available food source. Likewise, Boyi et al (2022) examined niche overlap in a co-occurring predators in the North Sea. Using a new 16S primer to metabarcode gut contents, they showed that the composition of fish prey in the diet of the Eurasian otter overlaps that of both harbour and grey seal diets, highlighting the possibility of interspecies competition where these species sharing foraging ground.…”
Section: Interaction Networkmentioning
confidence: 99%
“…, GenBank) to assign taxonomy to the organisms contributing to that environmental sample ( Baird & Hajibabaei, 2012 ; Taberlet et al, 2012 ; Thomsen & Willerslev, 2015 ). Analyses of eDNA have been used to quantify biodiversity ( Thomsen & Willerslev, 2015 ), determine species diets ( Boyi et al, 2022 ), and identify elusive species ( McClenaghan et al, 2020 ). Analyses of eDNA can also complement SIA-based estimations of source contributions to organic matter resources, such as detritus.…”
Section: Introductionmentioning
confidence: 99%